Admiral Matelieff's Singapore and Johor, 1606-1616 - Borschberg, Peter (NUS Press, 2016)
Cornelis Matelieff de Jonge (c.1570‒1632) was admiral of the Dutch East India Company when it sailed to Asia in 1605 and besieged Portuguese Melaka in 1606 with the help of Malay allies. A massive Portuguese armada then arrived from Goa to fight the Dutch and succeeded in breaking the siege on the Portuguese colony. Throughout this time, Matelieff penned a series of letters in which he provided a candid assessment of trading opportunities and politics in Asia. Admiral Matelieff's Singapore and Johor offers an edited selection of Matelieff’s most important writings from this period, focusing on his experience and interest in Singapore and the Straits of Melaka